Morphological Characteristics and Nutritional Quality of Mutant Benggala Grass (Panicum maximum cv Purple Guinea) Generation M1V3 - A. Fanindi; S. H. Sutjahjo; S. I. Aisyah; N. D. Purwanti (Tropical Animal Science Journal, 2022)
This study aims to observe morphological characters and genetic parameters of Benggala grass and its nutritional quality. Research on morphological characters was conducted at the Regional Technical Executive Unit (UPTD) of Tenjo dry land, using a randomized block design with 5 replications. The parents of the M1V3 mutant were from Benggala grass cv Purple guinea from the germplasm collection of the Indonesian Research Institute of Animal Production (Balitnak). The M1V3 plants were derived from 2400 M1V1 plants sorted to 250 M1V2 plants, and finally to 29 M1V3 plants. There were 29 plants planted on the experimental field using pols and control plants. Morphological observations and forage harvests were conducted at harvest/cutting ages 2 and 3 months after planting. Each harvest age was analyzed respectively. Forage quality observations were carried out at the RIAP Laboratory. The results showed that at the ages of 2 and 3 months, almost all characters were significantly different (p<0.05) in each genotype and several mutants of Benggala grass were higher than controls. Broad categorical genetic parameters were found in the characters of fresh weight, fresh weight of leaves, and fresh weight of tillers. Nutritional quality shows that irradiated plants have good nutritional quality because the value of crude protein and digestibility increases, while the value of crude fiber decreases compared to the control plant. In conclusion, the characterization of the M1V3 generation showed high-yielding mutants that were higher than the control and this M1V3 generation could be used as candidates for high-yielding varieties of Benggala grass.